2018
DOI: 10.3389/fmicb.2018.00069
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Non-additive Effects of Multiple Stressors on Autotroph C:N:P Ratios Propagate in Freshwater and Marine Food Webs

Abstract: A continuing challenge for scientists is to understand how multiple interactive stressor factors affect biological interactions, and subsequently, ecosystems–in ways not easily predicted by single factor studies. In this review, we have compiled and analyzed available research on how multiple stressor pairs composed of temperature (T), light (L), ultraviolet radiation (UVR), nutrients (Nut), carbon dioxide (CO2), dissolved organic carbon (DOC), and salinity (S) impact the stoichiometry of autotrophs which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…This search yielded 4899 hits. We also closely inspected all the primary studies mentioned in the 8 recent review papers including meta-analyses studies on elemental stoichiometry of phytoplankton in aquatic environment (Flynn et al, 2010;Hillebrand et al, 2013;Moreno and Martiny, 2018;Persson et al, 2010;Thrane et al, 2016;Villar-Argaiz et al, 2018;Yvon-Durocher et al, 2015). The list is also augmented with data from additional four studies that did not appear in the literature https://doi.org/10.5194/bg-2019-440 Preprint.…”
Section: Bibliographic Search and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…This search yielded 4899 hits. We also closely inspected all the primary studies mentioned in the 8 recent review papers including meta-analyses studies on elemental stoichiometry of phytoplankton in aquatic environment (Flynn et al, 2010;Hillebrand et al, 2013;Moreno and Martiny, 2018;Persson et al, 2010;Thrane et al, 2016;Villar-Argaiz et al, 2018;Yvon-Durocher et al, 2015). The list is also augmented with data from additional four studies that did not appear in the literature https://doi.org/10.5194/bg-2019-440 Preprint.…”
Section: Bibliographic Search and Screeningmentioning
confidence: 99%
“…For example, irradiance, temperature, and nutrient availability are often linked because the change in light availability will affect sea surface temperature, which in turn will alter vertical stratification in the water column and nutrient upwelling. Indeed, a meta-analysis on the pair-wise effects of environmental drivers on elemental stoichiometry of phytoplankton has shown that interactions of two environmental stressors can impose predominantly non-additive effects to C:N:P of phytoplankton, and that the effect of multiple environmental stressors is more than simply the sum of its parts (Villar-Argaiz et al, 2018). In addition, a recent multi-driver study carried for eight different drivers has shown that only a few dominant drivers can explain most of the evolutionary changes in population growth rates (Brennan et al, 2017).…”
Section: Implications For Global Biogeochemical Cyclesmentioning
confidence: 99%
“…Non-additive responses exhibit interactions between the effects of multiple stressors and are often complex and likely to be important in marine ecosystems, as demonstrated in studies of binary stressor combinations (e.g. Villar-Argaiz et al, 2018). The temporal aspects of short-lived versus continuous stressors, which may cause accumulated effects, should be taken into account.…”
Section: Box 33 Addressing Plastic Pollutionmentioning
confidence: 99%
“…, Villar‐Argaiz et al. ). More specifically, their possible antagonistic effects, for example, the mitigating effect of nutrients or temperature increases on the damaging effects of UVR observed in benthic marine algae (Marcoval et al.…”
mentioning
confidence: 99%